“It’s Freedom to Put Things Where My Mind Wants”: Understanding and Improving the User Experience of Structuring Data in Spreadsheets - Chalhoub, George; Sarkar, Advait (Proceedings of the ACM CHI Conference on Human Factors in Computing Systems, 2022)
Despite efforts to augment or replace the 2-dimensional spreadsheet grid with formal data structures such as arrays and tables to ease formula authoring and reduce errors, the flexible grid remains overwhelmingly successful. Why? We interviewed a diverse sample of 21 spreadsheet users about their use of structure in spreadsheets. It emerges that data structuring is subject to a complex network of incentives and constraints, including factors extrinsic to spreadsheets such as the user's expertise, auxiliary tools, and collaborator needs. Moreover, we find that table columns are an important abstraction, and that operations such as conditional formatting, data validation, and formula authoring can be implemented on table columns, rather than cell ranges. To probe this, we designed 4 click-through prototypes for a follow-up study with 20 participants. We found that although column operations improved the value proposition of structured tables, they are unlikely to supplant the advantages of the flexible grid.